Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3892/or.2016.4771
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of long non-coding RNA ANRIL inhibits the development of multidrug resistance in gastric cancer cells

Abstract: The development of multidrug resistance (MDR) is a crucial cause of therapy failure in gastric cancer, which results in disease recurrence and metastasis. Long non-coding RNAs (lncRNAs) have been proven to be critical in carcinogenesis and metastasis of gastric cancer. However, little is known about the roles of ANRIL (antisense non-coding RNA in the INK4 locus) in gastric cancer MDR. The aim of our study is to identify the biological function of ANRIL in gastric cancer MDR. In our results, ANRIL was highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 33 publications
(26 reference statements)
4
65
0
Order By: Relevance
“…Next, we detected several known lncRNAs involved in drug resistance in K562 and K562/ADM cells by qRT-PCR, such as HOTAIR [28], PVT1 [29], H19 [10], MALAT1 [30], UCA1 [11], CCAL [31], ANRIL [32], MEG3 [33] and FENDRR [12]. Interestingly, we found that FENDRR was mostly downregulated in K562/ADM cells compared with that in K562 cells ( Fig.…”
Section: Lncrna Fendrr Level Was Downregulated In Adriamycin-resistanmentioning
confidence: 85%
“…Next, we detected several known lncRNAs involved in drug resistance in K562 and K562/ADM cells by qRT-PCR, such as HOTAIR [28], PVT1 [29], H19 [10], MALAT1 [30], UCA1 [11], CCAL [31], ANRIL [32], MEG3 [33] and FENDRR [12]. Interestingly, we found that FENDRR was mostly downregulated in K562/ADM cells compared with that in K562 cells ( Fig.…”
Section: Lncrna Fendrr Level Was Downregulated In Adriamycin-resistanmentioning
confidence: 85%
“…Lan et al found that ANRIL was greatly upregulated in cisplatin resistant and 5-Fu resistant patients. The rate of tumor growth significantly decreased after transfected with si-ANRIL, and the levels of MDR1, MRP1 also reduced [74]. …”
Section: Long Non-coding Rna In Cancer Cell Drug Resistancementioning
confidence: 99%
“…LncRNA SNHG5 reduced DDP sensitivity of BGC823 and SGC7901 gastric cancer cells through up-regulating expression of MDR1, MRP1 and Bax as well as downregulating Bcl-2 expression [164]. In addition, lncRNAs GHET 1 [165], AK022798 [166], antisense non-coding RNA in the INK4 locus (ANRIL) [167], UCA 1 [168] and HULC [169] also conferred DDP resistance of gastric cancer cells via modulating expression of multiple drug resistance-related genes. LncRNA HOTAIR, which was significantly up-regulated in DDPresistant gastric cancer cells and tissues, could regulate chromatin status and contribute to DDP resistance of gastric cancer, through activating PI3K/Akt/MRP1 and Wnt/ ÎČ-catenin signaling pathways [170,171].…”
Section: Lncrnas and Resistance To Platinum Drugsmentioning
confidence: 99%